2018
DOI: 10.1021/acs.macromol.8b02619
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar Aggregation Features in Poly(3-hexylthiophene)/Chlorobenzene Solutions

Abstract: We report on anomalous structure and relaxation features of the aggregate clusters fostered in a representative series of dilute poly­(3-hexylthiophene)/chlorobenzene (P3HT/CB) solutions (3, 5, 8, and 10 mg/mL), as resolved by multiscale dynamic/static analysis schemes including depolarized/polarized dynamic light scattering (DDLS/DLS), static light/X-ray scattering (SALS/SLS/SAXS), and scanning transmission electron/transmission electron microscopy (STEM/TEM). DLS/DDLS analyses reveal the coexistence and dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 69 publications
(108 reference statements)
1
19
0
Order By: Relevance
“…[20] It must be emphasized that the polymer aggregates tend to be reformed spontaneously after each filtration. [21] Therefore, care must be taken when using these fraction values extracted from filtration experiments. Nevertheless, the results demonstrate in a semi-quantitative way that a low T dis is capable of sufficiently enhancing the polymer aggregation in solution, which is not only in excellent agreement with the solution absorption (Figure 1 b) but also strongly supports the variations in fibril width, p-p stacking interactions, and field-effect mobility (Figures 2 and 3).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[20] It must be emphasized that the polymer aggregates tend to be reformed spontaneously after each filtration. [21] Therefore, care must be taken when using these fraction values extracted from filtration experiments. Nevertheless, the results demonstrate in a semi-quantitative way that a low T dis is capable of sufficiently enhancing the polymer aggregation in solution, which is not only in excellent agreement with the solution absorption (Figure 1 b) but also strongly supports the variations in fibril width, p-p stacking interactions, and field-effect mobility (Figures 2 and 3).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In all cases, the average size of the aggregates is roughly on the order of a few hundred nanometers, which seems larger than the value of the PffBT4T‐2DT derivative PffBT4T‐2OD, characterized by small‐angle neutron scattering (≈40 nm) . It must be emphasized that the polymer aggregates tend to be reformed spontaneously after each filtration . Therefore, care must be taken when using these fraction values extracted from filtration experiments.…”
Section: Resultsmentioning
confidence: 93%
“…The aggregate species clearly is unfavorable for controlling chain orientation in electrospun nanofibers, as we discuss later in the X-ray diffraction (XRD) and photoluminescence (PL) analyses. The q -independent slow mode, ubiquitous in all three P3HT solutions investigated, might reflect the contribution of nondiffusive, microsized clusters that undergo a dynamic condensation/decomposition alternating process [9]. Judged solely by the apparent relaxation time along with the solvent viscosity, the cluster size appears to follow the order: TCB < CF < CB.…”
Section: Resultsmentioning
confidence: 99%
“…Among the parameters during the solution process, the processing solvent plays a critical role during thin-film formation due to the variation of chain conformation in the pristine solution [9,10]. It has been reported that P3HT chains preferentially adopt an edge-on orientation with π−π stacking parallel to the substrate, which allows the holes hopping between polymer chains to be the main transport mechanism in P3HT thin films.…”
Section: Introductionmentioning
confidence: 99%